Otimização de um sistema procarioto para a expressão da rMEPLox: um antígeno não tóxico promissor para a produção de antiveneno loxoscélico. - Rafael Jose Luis Saavedra Langer (2021)
Loxoscelism is the most dangerous araneism form in Brazil and antivenom therapy is the recommended treatment. Antivenom is produced by horse immunization with Loxosceles spider venom, which is toxic for the producer animal. Moreover, due to the high amount of venom required for horse hyperimmunization, new strategies for antigens obtention have been proposed. In this sense, our research group has previously produced a non-toxic recombinant multiepitopic protein (rMEPLox) derived from Loxosceles toxins. rMEPLox was a successful immunogen, being able to induce the production of neutralizing antibodies, which could be used in the Loxoscelism treatment. However, rMEPLox obtention procedure requires optimization, as its production needs to be scaled up to suit antivenom manufacture. Therefore, an effective protocol development for rMEPlox production would be advantageous. To achieve this objective, we evaluated the influence of different cultivation conditions for rMEPLox optimum expression whichwere defined as the use of C43(DE3)pLysS as a host strain, 2xTY medium, 0.6 mM IPTG, biomass pre induction of OD600nm = 0.4 and incubation at 30 °C for 16 h. Following the optimized protocol, 39.84 mg/L of soluble rMEPLox was obtained and tested as immunogen. The results show that the obtained rMEPLox preserved the previously described immunogenicity, and it was able to generate antibodies that recognize different epitopes of the main Loxosceles venom toxins, which makes it a promising candidate for the antivenom production for loxoscelism treatment.